Feasability Study on Phytoremediation in Treatment of Open Landfill Leachate - Ismail, Abustan; Mohd Yuhyi, Mohd Tadza; Mohd Tadza, Abdul Rahman (Penerbit Universiti Sains Malaysia, 2015)
Phytoremediation is an emerging technology that utilize the potential of green plants and their associated microorganisms to detoxify, remediate and stabilize potential contaminants in leachate.